20.0k views
12 votes

( √(40) )/( √(3) )


User Ekow
by
4.9k points

1 Answer

9 votes

Answer:


( √(40) )/( √(3) ) =(2√(30) )/( 3 )

Explanation:

Given


( √(40) )/( √(3) )

Required

Simplify


( √(40) )/( √(3) )

Rationalize:


( √(40) )/( √(3) ) =( √(40) )/( √(3) )*( √(3) )/( √(3) )


( √(40) )/( √(3) ) =( √(40*3) )/( √(3*3) )


( √(40) )/( √(3) ) =( √(120) )/( √(9) )


( √(40) )/( √(3) ) =( √(120) )/( 3 )

Expand the numerator


( √(40) )/( √(3) ) =( √(4*30) )/( 3 )


( √(40) )/( √(3) ) =( √(4)*√(30) )/( 3 )


( √(40) )/( √(3) ) =( 2*√(30) )/( 3 )


( √(40) )/( √(3) ) =(2√(30) )/( 3 )